Growth and Yield Response of Bambara Groundnuts (Vigna subterranea L ) to the Mixed of Peat and Mineral Soil with Several Dosage of Dolomite - Pamungkas, Inggi; Turmudi, Edhi; Hindarto, Kanang Setyo (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2017)
Bambara groundnut (Bogor groundnut) was an alternative food crops having high nourishing, better taste and bigger size nut than the soy beans and peanuts. To meet the need for food and industrial needs, the program to increase production of Bogor groundnut was required, one of which is the use of peat as a growing medium using the technology of mixing peat and mineral soil. The research objective was to obtain a mixture of peat with mineral soil and dolomite lime dose suitable for the highest growth and yield of Bogor groundnut. This study was conducted in May 2015-September 2015 in the Greenhouses of Faculty of Agriculture, University of Bengkulu. The experiment was arranged in a completely slot deposit 5000 randomized design (CRD) with two treatment factors and three replications. The first factor was soil mix of peat and mineral soil (G0: 100% peat + 0% mineral soil; G1: 75% peat + 25% mineral soil; G2: 50% peat + 50% mineral soil; G3: 25% peat + 75% mineral soil) and the second factor was the dose of dolomite (D0: without lime dolomite; D1: 3 ton ha-1 and D2: 4 ton ha-1). The results showed that the response of biomass dry-weight to a mixture of peat with mineral soil was influenced by the dose of dolomite, but there was no interaction on other variables. Treatment of a mixture of peat 100% alone was capable of generating the highest number of leaf, biomass fresh- and dry-weight. Bogor groundnut plants showed the same response to the dose variation of dolomite lime. Keywords: Bogor groundnut, peat, mineral, dolomite